Matching in Housing Markets: The Role of Ethnic Social Networks - Agarwal, Sumit; Choi, Hyun-Soo; He, Jia; Sing, Tien Foo (Review of Financial Studies, 2019)
This paper investigates the role of ethnic matching between buyers and sellers in Singapore’s public housing market. We find that sellers sell homes in blocks with a high concentration of their own (other) ethnic group(s) at significant premiums (discounts). Chinese sellers earn 1.7% higher premiums when selling homes to Chinese buyers in high Chinese concentrations housing blocks, but Malay sellers accept 1.6% discounts from Malay buyers in the same blocks. We find that the high volume of within-ethnicity transactions with the price discounts is supported by the ethnic social networks, that is, through ethnicity-specialized real estate agents. Received May 3, 2017; editorial decision July 4, 2018 by Editor Stijn Van Nieuwerburgh.